(untitled) (BIRDEM Medical Journal, 2012)
Nonalcoholic fatty liver disease (NAFLD) may be the most common liver disease in the world, with a high prevalence in the obese, type 2 diabetic populations, and it is probably underestimated as a cause for cirrhosis. Clinicopathologically, it represents a wide spectrum of histologic abnormalities and clinical outcomes, ranging from benign hepatic steatosis to cirrhosis. Pathophysiologically, insulin resistance is thought to be pivotal in the development of steatosis, after which a second oxidative stressor produces lipid peroxidation and nonalcoholic steatohepatitis (NASH). Liver biopsy is the gold standard for diagnosis and prognosis. The need for an effective treatment is both clear and urgent, yet in the absence of proven therapies, treatment is directed toward weight loss and comorbidity management. For patients with NAFLD at risk of disease progression, there is a lack of large, randomized, placebo-controlled trials of adequate treatment duration, with baseline stratification according to histologic severity. DOI: http://dx.doi.org/10.3329/birdem.v2i1.12360 Birdem Med J 2012; 2(1) 33-43